Metabolic Syndrome and Objective Physical Performance Measures in Mid-to-Early Late Life Women: SWAN. (17th December 2021) - Strotmeyer, Elsa; Boudreau, Robert; Lange-Maia, Brittney; El Khoudary, Samar; Ylitalo, Kelly; Kriska, Andrea; Karvonen-Gutierrez, Carrie; Napoleone, Jenna
Abstract: Metabolic syndrome (MetS) is a cluster of factors (hypertension, abdominal obesity, impaired fasting glucose, low high-density lipoprotein, hypertriglyceridemia). How midlife MetS impacts future physical functioning is uncertain. We hypothesized that higher midlife MetS components are associated with poorer physical performance in early late life for multi-ethnic women. MetS status from 1996-2011 (8 visits) and objective physical performance (2015/16; short physical performance battery (SPPB; 0-12), 40-foot walk (m/s), 4-meter gait speed (m/s), chair stands (sec), stair climb (sec)) were assessed in the Study of Women's Health Across the Nation (SWAN; n=1722; age 65.4±2.7 years; 26.9% Black, 10.1% Chinese, 9.8% Japanese, 5.5% Hispanic). Poisson latent class growth modeling identified trajectory groups distinguishable by number of MetS components: none (23.9%), 1=low-MetS (28.7%), 2=mid-MetS (30.9%), >3=high-MetS (16.5%). High-MetS versus none had higher body mass index, pain, financial strain, and lower physical activity and self-reported health (p < 0.0001). Black and Hispanic women were more likely to be in high-MetS and had worse physical functioning, along with Chinese women, versus White (all p<0.05, except gait speed in Hispanic). Adjusted linear regression related MetS groups to physical performance. High-MetS versus none demonstrated adjusted worse 40-ft walk (β:-0.08; 95% CI:-0.13, -0.03), gait speed (β:-0.09; 95% CI:-0.15, -0.02), SPPB (β:-0.79; 95% CI: -1.15, -0.44), and chair stands (β:0.69; 95% CI: 0.09, 1.28), but not stair climb, with race significantly related to all except 40-ft walk. Midlife MetS trajectories related to poor physical performance in early late life multi-ethnic women. Managing midlife metabolic function may improve physical performance in late life.